Pancreatic Rupture in Mid-Pregnancy Mimicking Obstetric Emergency - Ahmad Bukhoeri; Putri Sekar Wiyati; Lubena Lubena; Ahmad Fathi Fuadi (International Journal Labs, 2026)
Suspicion for non?obstetric intra?abdominal injuries in pregnant patients is often overlooked due to the striking clinical similarity to more common obstetric causes such as placental abruption or uterine rupture. This report discusses diagnostic pitfalls in a fatal pancreatic rupture case masquerading as a catastrophic obstetric event. This case highlights the